The Forest Resources Information System to Support Sustainable Forest Management: Case Study Perum Perhutani - Ahsana Riska; Muhamad Buce Saleh; Hendrayanto Hendrayanto (Institut Pertanian Bogor (IPB University), 2016)
Forest resources information system aims to provide accurate and complete information periodically to support effective and efficient decision-making process. Perum Perhutani is the oldest state-owned enterprise for forestry in Indonesia. They have been developed sustainable forest management include the information system. Although forest resources information system already exists, forest quality decreases time by time. This research study aims to improve the effectiveness of forest resources information system in Perum Perhutani related to forest resources management. This study focused the observation on 1) mechanism and supporting variables of forest resources information system and 2) influence of forest resources information system on the decision-making process. Mechanism and supporting variables of forest resources information system show how is forest resources information system been working to support the decision-making process. The research was conducted by reviewing literature and depth interviewing with key informants. The results showed that the current forest resources information system could not support sustainable forest management in Perum Perhutani. This information system has weakness in data and information, procedures, technology, and user. Decision-making process highly adopts technocratic paradigm, centralized, and technically dominated by decision-maker preferences which give direct affect on information management at the site level. Forest management unit as a manager at the site level become information provider but have no authority to use information to decide management Keywords: